Fluktuasi Suhu dan Kelembaban Tanah pada Berbagai Tipe Penggunaan Lahan Pertanian: Implikasi Sifat Fisik Tanah - Riskawati; Azalia Fajri Yasin; Fredy Titit (Jurnal Galung Tropika, 2025)
Climate change impacts all aspects of life including agriculture, which influences land management practices, soil temperature and moisture, and land use types. This research aims to identify soil temperature and moisture fluctuations across various agricultural land cover types and their relationship to soil physical properties. This research was conducted in Mariat District, Sorong Regency, on four types of land use and was selected intentionally (purposive sampling). The coordinates of each type of land are: Rice Field 075°77’35’’E 98°88’12”SL; Garden land: 075°75’82”E, 98°88’09”SL; Agroforestry land: 075°74’30”E, 98°88’01”SL; and Unproductive land 075°76’30”E, 98°88’80”SL. Measurement of soil temperature and humidity using environment-meter for 30 consecutive days and soil sampling was carried out (intact soil samples and disturbed soil samples) to identify the physical properties of the soil. The research results showed fluctuations in soil temperature and moisture content across each land use. In general, the average morning temperature was 27.2°C, midday 32°C, and evening 27.5°C. Meanwhile, the average soil moisture content was 79.5% in the morning, 74% in the afternoon, and 81% in the evening. The physical properties of the soil in the four land uses are different in soil texture, soil color, available water, permeability, and aggregate stability. The use of rice fields and dry fields has the same temperature and humidity. However, the use of gardens and agroforestry land tends to differ because variations influence plant vegetation. Temperatures too high and humidity too low can worsen soil conditions, causing physical degradation that affects agricultural productivity and soil sustainability.